Nonfatal Agricultural Injuries in Florida: Support Activities for Crop and Animal Production - Robert Overstreet; Cassandra Ward; Serap Gorucu (EDIS)
This publication examines nonfatal injuries and illnesses resulting from support activities for crop production and animal production workers in Florida. Written by Robert Overstreet, Cassandra Ward, and Serap Gorucu, and published by the UF/IFAS Department of Agricultural and Biological Engineering, July 2022.